2010
DOI: 10.1055/s-0029-1245184
|View full text |Cite
|
Sign up to set email alerts
|

Zuverlässigkeitsprüfung eines Messverfahrens zur Charakterisierung des Standverhaltens und Quantifizierung des Balancevermögens auf einer instabilen Plattform (Posturomed)

Abstract: The Posturomed Platform can be used to evaluate stance ability and characterise the patterns of one legged stance. The measurements are reproducible, but include a small learning effect. Further studies including EMG could provide more understanding of neuromuscular control mechanisms and their adaption to training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 7 publications
2
13
0
Order By: Relevance
“…As sensorimotor training is known to improve the reaction of individuals to sudden disturbances of the support surface [ 10 ], we attribute a major contribution to the improved stabilization capacity of our patients to sensorimotor training but recognise potential time or learning effects may also play a role. While our results are consistent with those reported by Boeer et al [ 22 ], we evaluated stabilization capacity during bipedal, rather than unipedal, stance since the majority of participants in our study were unable to stand on one leg without aid.…”
Section: Discussionsupporting
confidence: 89%
“…As sensorimotor training is known to improve the reaction of individuals to sudden disturbances of the support surface [ 10 ], we attribute a major contribution to the improved stabilization capacity of our patients to sensorimotor training but recognise potential time or learning effects may also play a role. While our results are consistent with those reported by Boeer et al [ 22 ], we evaluated stabilization capacity during bipedal, rather than unipedal, stance since the majority of participants in our study were unable to stand on one leg without aid.…”
Section: Discussionsupporting
confidence: 89%
“…This indicates that there was no learning effect for AP or ML direction and was confirmed when considering inter- and intra-subject variations. In contrast, another study found slight and non-significant decreases of pathways within the course of five trials [ 22 ]. This study also used the Posturomed, but the platform pathway was analyzed for six seconds and the setup did not include unexpected perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…No generally decreasing or increasing magnitudes were observed descriptively within all 12 trials per session, indicating neither improving nor deteriorating dynamic balance responses. Boeer et al [ 22 ] examined balance ability using the Posturomed, however measuring total platform pathway with no perturbation during single leg stance. They performed retests after one to three weeks and found slight but not significant decreases within the course of five consecutive trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postural stability was assessed with different tests. First, postural control was evaluated on a balance device (Posturomed) that allowed platform sway in the transversal plane (for technical details see Mueller et al, 2004 ) and was shown to have good test-retest reliability (Boeer et al, 2010 ). For this purpose, participants stood with one leg on the free-swinging device and were asked to sway as little as possible during the measurement period of 15 s. A period of 15 s was chosen due to the fact that longer exposures than 15 s may lead to fatigue, especially in participants that struggle to keep their balance on this device.…”
Section: Methodsmentioning
confidence: 99%